Development of a hydrophobic coating for the porous gas diffusion layer in a PEM-based electrochemical hydrogen pump to mitigate anode flooding - Lee, Myoungseok; Huang, Xinyu (Electrochemistry communications, 2019)
Anode flooding is one of the critical issues in developing a proton exchange membrane (PEM)-based electrochemical hydrogen pump. Improving the hydrophobicity of the gas diffusion layer (GDL) has been studied as an approach to mitigating anode flooding in electrochemical pumps. A mixture of Nafion™ and oxidized carbon nanotubes (O-CNT) has been applied to the porous gas diffusion medium in the hydrogen pump cell. The coating renders the GDL hydrophobic with an effective contact angle of 130°. Electrochemical pump testing has shown that, with the help of the coating, the flood-recovery performance of the hydrogen pump was greatly improved. A hydrogen pump cell with an uncoated GDL was not able to recover from a flooded state, while a hydrogen pump cell with a coated GDL was able to recover its performance in about 100 s. •Anode flooding is a critical issue in low-temperature electrochemical hydrogen pumps based on proton exchange membranes.•Coating the gas diffusion medium with a mixture of Nafion and oxidized carbon nanotubes (O-CNT) renders it highly hydrophobic.•The Nafion/O-CNT coating effectively eliminated anode flooding.